Negative Thermal Quenching and Size‐Dependent Optical Characteristics of Highly Luminescent Phosphorene Nanocrystals. Issue 12 (17th April 2020) - Jana, Subhajit; Mukherjee, Subhrajit; Ghorai, Arup; Bhaktha, Shivakiran B. N.; Ray, Samit Kumar
Abstract: Highly luminescent and direct band gap black phosphorus (BP) nanocrystals (NCs) synthesized using a cost‐effective sonochemical exfoliation route are reported. Microscopic studies have confirmed the exfoliation of few‐layer nanoflakes and BP NCs with variable average size between ≈2 and ≈8 nm. Structural and vibrational characteristics reveal the superior crystalline quality by retaining the phase and crystalline symmetry in NCs. Size‐dependent absorption characteristics are observed by controlling the nanoparticle size and show a progressive blue shift near band edge absorption on reducing the size, useful for selective multicolor photodetection. Temperature‐dependent photoluminescence measurements from room temperature (300 K) down to 10 K are performed. Most interestingly, BP NCs with the lowest diameter exhibit a novel negative thermal quenching behavior as compared to positive thermal quenching observed usually in bulk semiconductors and BP NCs with larger diameter. Metal–semiconductor–metal type (Au/BP‐NCs/Au) photodetectors are fabricated to study their photoresponse properties, which reveal the potential application of BP NCs as optical modulators. Abstract : Size‐dependent behavior of photolumenescence depending on the fraction of oxidized proportion of phosphorene nanocrystals is reported. Experimental findings on novel thermal quenching of photolumenescence are explained by radiative surface defect states and deep‐level intermediate states. As‐synthesized nanocrystals are employed for metal–semiconductor–metal‐type photodetecting device, showing good photoresponse.